DISCURSO DA MARCA: uma abordagem da semiose comunicacional da marca - ALVES, Victor Hugo Lima (2015)
The thesis broachs the constituition of the trademark’s meaning on a perspective of its speech in the consumer society. Through proposed goals, (a) The description of the brand’s communicative process as a social speech; (b) The demonstration of the constituition of the brand’s meaning by the circulation of useful effect; and (c) An articulation of the social theory that bases the process; The intention is to explore it as a theoretical explanatory possibility through the speech in the social semiosis. The thesis is justified through the development of the communicative approach to the constituition of the trademark’s meaning (theoretical relevance) and through the possibility of intervention in the social reality from the knowledge of how the brand is instituted as a social speech (social relevance). It’s about a theoretical work, of qualitative nature, from an exploratory research, proposing the construction of a brand’s semiosis. It was concluded that the constituition of the comtemporary brand’s meaning essentially by a process of production of social sense in the consumer society is theoretically pertinent.